1 Henry Dutton, A Revision of Swift's Digest of the Laws of Connecticut 564 (1871) - (:unkn) unknown (My University, 1871)
A person, before he trusts a gun with an incautious person, is bound to render it perfectly innoxious.
Keywords: TRANSFER